2018
DOI: 10.1063/1.5026899
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and formation of lanthanum-hydrocarbon radicals formed by association and carbon-carbon bond cleavage of isoprene

Abstract: Right click to open a feedback form in a new tab to let us know how this document benefits you.La atom reaction with isoprene is carried out in a laser-vaporization molecular beam source. The reaction yields an adduct as the major product and C− −C cleaved and dehydrogenated species as the minor ones. La(C 5 H 8 ), La(C 2 H 2 ), and La(C 3 H 4 ) are characterized with mass-analyzed threshold ionization (MATI) spectroscopy and quantum chemical computations. The MATI spectra of all three species exhibit a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Gas-phase titanium oxide clusters can be used as ideal models of the active sites on titania materials. The structures and reactivity of small to nanosized titanium oxide clusters have been extensively studied. The study of the interactions of titanium oxide clusters with CO under dark conditions demonstrated the outstanding reactivity of the titanium oxide clusters with specific compositions ((TiO 2 ) x O – and (TiO 2 ) x + ) that have atomic oxygen radical anions (O •– ) as the active sites. , It has been proposed that (TiO 2 ) x O – clusters with x values of up to 50 still have the O •– radicals . Although there have been many studies on the reactivity of titanium oxide clusters under dark conditions, the photoactivity of these oxide clusters has been almost untouched …”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase titanium oxide clusters can be used as ideal models of the active sites on titania materials. The structures and reactivity of small to nanosized titanium oxide clusters have been extensively studied. The study of the interactions of titanium oxide clusters with CO under dark conditions demonstrated the outstanding reactivity of the titanium oxide clusters with specific compositions ((TiO 2 ) x O – and (TiO 2 ) x + ) that have atomic oxygen radical anions (O •– ) as the active sites. , It has been proposed that (TiO 2 ) x O – clusters with x values of up to 50 still have the O •– radicals . Although there have been many studies on the reactivity of titanium oxide clusters under dark conditions, the photoactivity of these oxide clusters has been almost untouched …”
Section: Introductionmentioning
confidence: 99%
“…Gas phase studies on atomic clusters provide an ideal arena for probing chemical activities and mechanisms in an unperturbed environment. Iron oxide clusters, with unique magnetic, biochemical and catalytic properties, have attracted broad interest in gas phase studies with mass spectrometry, spectroscopy, and quantum chemistry calculations. The reactions of positively charged iron oxide clusters with isoprene have been studied, and the size-dependent reactivity has been identified . The net charge can affect the cluster reactivity significantly. Neutral clusters are good models for the active sites of bulk metal oxides without charge effects .…”
Section: Introductionmentioning
confidence: 99%